Konseling Behavioral dengan Strategi Self Management untuk Meningkatkan Kemandirian - Antara, Made Pradnyana; Dharsana, I Ketut; Suarni, Ni Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2019)
This study was aimed to know whether the behavioral counseling by using self-management strategy was effective to improve self-autonomy students through lesson study toward grade XI IPA students of SMA Negeri 1 Sukasada and to know the difference between students who were given behavioral counseling by using self-management strategy and the students who were not given the treatment. This type of the research was quasi experimental design with nonequivalent pre-test post-test control group design. The technique of the sampling used was random sampling and random class as the intact group. This study used two classes, XI IPA 1 with 18 students as the experimental class and XI IPA 2 with 18 students as the control class. The process of data collection in this study used the observation methods, interviews, diaries and self-esteem autonomy patterns of linkert scale and analyzed descriptively for statistical analysis used the t-test formula. To test the hypothesis, it was used the t test, with the results in the first hypothesis which found that tcount> ttable (10.86> 1.739) which meant that there was effectiveness of the implementation of behavioral counseling theory by using self-management strategy to improve self-autonomy through lesson study toward the students of XI IPA 1 and the result of the second hypothesis found that tcount> ttable (8.70> 2.03) which meant that there was a difference of self-autonomy between the students who were given behavioral counseling by using self-management strategy and the students who were not given behavioral counseling by using self-management strategy toward grade XI IPA students of SMA Negeri 1 Sukasada.Â Keywords: behavioral conseling, Self-Management Strategy , Self-Autonomy